Negative shift in the evaluation of an ethnonym: Hypothesis of contextual conditioning and measurement tools - E. S. Gromenko; M. A. Krongauz (Шаги, 2025)
The article examines the hypothesis of contextual conditionality linking the assessment of an ethnonym with the context. The assumption that words with negative connotation gravitate towards negative contexts is tested. This means, in particular, that quantitative processing of contexts can become the basis for identifying a negative tone and its quantitative qualification, i.e. the greater the percentage of negative contexts, the more intense is the negative connotation in the semantics of the word. The purpose of the study is to describe the quantitative distribution by type of context (positive, neutral and negative) of four ethnonyms: Asiatic, European, Italian, Tajik, and to offer a meaningful interpretation of this distribution. In response to this goal, the study clarifies assessments of context. Thus, firstly, among various understandings of the negativity of the context, one is selected («narrow contextual tonality»), and secondly, objective criteria for qualifying the context as negative are developed. The research material consisted of about 900 texts of comments and posts obtained by a continuous sampling method for lexical and grammatical search for the lexemes European, Asiatic, Tajik, Italian in the subcorpus of Social networks of the National Corpus of the Russian Language. An additional method for assessing the negativity of an ethnonym is considered: replacing a negative word with a euphemism. For names of ethnic groups, such a neutral eplacement is the construction of a person of ... nationality.